Crowd assisted networking and computing - Pathan, Al-Sakib Khan (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
Crowd computing, crowdsourcing, crowd-associated network (CrAN), crowd-assisted sensing are some examples of crowd-based concepts that harness the power of people on the web or connected via web-like infrastructure to do tasks that are often difficult for individual users or computers to do alone. This creates many challenging issues like assessing reliability and correctness of crowd generated information, delivery of data and information via crowd, middleware for supporting crowdsourcing and crowd computing tasks, crowd associated networking and its security, Quality of Information (QoI) issues, etc. This book compiles the latest advances in the relevant fields--
Includes bibliographical references and index.
Keywords: Crowdsourcing